Kepatuhan Indonesia Terhadap Perjanjian Internasional Mengenai Isu Lingkungan Hidup yang Berdampak Pada Perubahan Iklim, Studi Kasus: Deforestasi Jambi dan Riau - Pratama, Muhammad Wirya; Windiani, Reni (Journal of International Relations, 2020)
The Purpose of this study is to determine Indonesia’s compliance with international agreements, namely the Kyoto Protocol on environmental issues in the Riau and Jambi regions. This environmental issue led Indonesia to ratify the Kyoto Protocol contained in Law Number 17 of 2004 to reduce carbon emissions which until now has not seen any results. Therefore this research aims to find out whether Indonesia complies with international treaties that have been ratified and endorsed. The concept that used in this study is the concept of compliance with 3 (three) main indicators, namely : Output, Outcome, and Impact. This research will use a qualitative method that analyze how obedient Indonesia against international agreement specifically Kyoto Protocol on environmental issues which is currently quite interesting to considered in Indonesia, especially in the Riau and Jambi regions. This research began in the year of 2004 to 2015. On the other hand, Indonesia is in the category of passive comply, which shows that Indonesia’s ability is in the comply position but not directly and focused. So, in the other words, Indonesia tends to be difficult to comply with this Kyoto Protocol.